A hermeneutic-phenomenological analysis of teachers' learning experiences through the observation of a professional basketball coach's coaching session. Issue 1 (2nd January 2021) - Matsuyama, Naoki
ABSTRACT: In this study, the learning experiences of four elementary school teachers who were basketball coaches were explored. Specifically, the learning experiences gained through observing professional basketball coaches' sessions were examined by employing van Manen's hermeneutic-phenomenological approach, which focuses on the thematic analysis of lived experiences. Previous coaching studies that have focused on the professional development of coaches have revealed that observing elite coaching sessions could be a major source of practical coaching knowledge because coaches could learn from experienced coaches. Quantitative studies of this learning effect have revealed that observers learn new coaching methods from a general perspective. However, this study revealed that teachers give specific meaning and value to observed phenomena from the perspective of personal interest based on their coaching or teaching beliefs. This learning was interpreted from a multifaceted perspective, which was evident from their coaching interests and questions. This study disclosed that teachers reflect on their coaching philosophy, methods and attitude. Furthermore, even if teachers generally tend to highlight their coaching methods, this has a qualitatively complex nature because the meaning and value given to coaching methods varied in each teacher's reflection. The perspective of problem-solving highlighted how to answer their personal questions based on practical coaching problems by observing a coaching session. Discovering the methodological differences between the observation session and the daily coaching session were highlighted.